Long‐term outcomes of primary sclerosing cholangitis: an Australian non‐transplant tertiary hospital perspective. Issue 3 (21st March 2019) - Freeman, Elliot; Majeed, Ammar; Kemp, William; Roberts, Stuart K.
Abstract: Background: There are limited Australian epidemiological and outcome data on primary sclerosing cholangitis (PSC), with the only published study involving a state liver transplantation service. Aim: The aim of this retrospective study was to evaluate the natural history, and morbidity and mortality of PSC in an Australian population managed in a large metropolitan non‐transplant teaching hospital. Methods: We identified all PSC patients managed at The Alfred Hospital over a 10‐year period and analysed their clinical and demographic data. Primary outcomes were liver transplantation and death. Secondary outcomes included cholangiocarcinoma, development of cirrhosis, liver decompensation, cholangitis requiring hospital admission and the development of dominant strictures requiring dilatation. Results: We identified 39 PSC patients (69% male) with a median follow‐up time of 63 months (range 5–289). Median age at diagnosis was 45 years (range 10–81) and 29 (74%) patients had concurrent inflammatory bowel disease. Five patients had cirrhosis at diagnosis and 10 (26%) developed cirrhosis after a median follow up of 54 months. Three (8%) patients developed cholangiocarcinoma and one with overlap syndrome required liver transplantation. The 10‐ and 20‐year survival rates for the entire cohort were 77.4% (95% confidence interval 55.6–89.4) and 68.8% (95% confidence interval 42.1–85) respectively. Survival in patients with small‐duct disease was not different from those without. Conclusion: Although the PSC population in this Australian cohort appears typical of the disease, rates of liver decompensation are relatively low and the overall transplant‐free survival may be better than that reported in overseas cohorts or from cohorts derived from liver transplantation centres.